2022
DOI: 10.1021/acs.jpclett.2c03292
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced C–C Bond Cleavage toward Efficient Ethanol Electrooxidation

Abstract: Ethanol, as a sustainable biomass fuel, is endowed with the merits of theoretically high energy density and environmental friendliness yet suffers from sluggish kinetics and low selectivity toward the desired complete electrooxidation (C1 pathway). Here, the localized surface plasmon resonance (LSPR) effect is explored as a manipulating knob to boost electrocatalytic ethanol oxidation reaction in alkaline media under ambient conditions by appropriate visible light. Under illumination, Au@Pt nanoparticles with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…2g), and similar phenomena have been reported in the literature. 69 In addition, NP AuPd under 400–800 nm light irradiation achieved an EOR activity comparable to that at 40–46 °C solution temperatures (Fig. 2f).…”
Section: Resultsmentioning
confidence: 68%
“…2g), and similar phenomena have been reported in the literature. 69 In addition, NP AuPd under 400–800 nm light irradiation achieved an EOR activity comparable to that at 40–46 °C solution temperatures (Fig. 2f).…”
Section: Resultsmentioning
confidence: 68%
“…As illustrated, electrocatalysis of EtOH generates two strong peaks in the forward and reverse sweeps. The first peaks were generated because of the decomposition of EtOH molecules at the surface of four samples. , These interactions not only delivered the high current density but also produced the carbonaceous intermediates . Hence, other peaks appeared in backward scans because of the elimination of produced carbonaceous intermediates.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, other peaks appeared in backward scans because of the elimination of produced carbonaceous intermediates. Subsequently, it can be logically concluded that the current density ratio generated in the forward ( J f ) to reverse ( J b ) scans can be used as a reliable parameter to evaluate the power of an electrocatalyst. , By comparing the achieved plots, the Pd 92 Co 8 aerogel ( J f / J b = 1.17), Pd 95 Co 5 aerogel ( J f / J b = 1.13), and Pd 89 Co 11 aerogel ( J f / J b = 0.96) reveal a stronger tolerance to poisoning relative to Pd/C ( J f / J b = 0.6). Additionally, the decomposition reaction of EtOH for Pd 92 Co 8 aerogel (−0.548 V), Pd 95 Co 5 aerogel (−0.538 V), and Pd 89 Co 11 aerogel (−0.532 V) started at a more negative potential in comparison to Pd/C (−0.460 V), corroborating the improved kinetics for these resultant 3D superstructures. , Moreover, the Pd 92 Co 8 aerogel, Pd 95 Co 5 aerogel, Pd 89 Co 11 aerogel, and Pd/C generated the mass activity of 4302.1, 3380.9, 2135.1, and 1007.9 mA/mg Pd .…”
Section: Resultsmentioning
confidence: 99%
“…These high activities are due to the interaction of all electrocatalysts with the clean available active sites. However, the cleavage of CH 3 CH 2 OH molecules leads not only to the generation and adsorption of intermediate species on the aerogel surface but also to a sharp decrease in the specific activity owing to the poisoning and blocking of the active sites. The steeper slope of the CA profile for Pt–Ag aerogel suggests a greater poisoning and less stability against Pd–Ag aerogel. Additionally, the gradual decrease in CA plots for both engineered aerogels relative to the Pd/C catalyst highlights their incredible electrocatalytic durability.…”
Section: Resultsmentioning
confidence: 99%